Reducing child malnutrition through mother's birth spacing: evidence from Ghana - Essilfie, Gloria; Kofinti, Raymond Elikplim; Asmah, Emmanuel Ekow (DHS Working Papers No. 193, 2023)
Although research has focused on the impact of birth spacing on maternal health, inadequate maternal repletion due to shorter birth intervals could also affect the health of the child. However, limited studies exist on the linkage between birth spacing and child nutrition. This study examines the association between birth spacing and child stunting and underweight using the 2014 Ghana Demographic and Health Survey. The study employed descriptive statistics and logistic regressions to establish the association between birth spacing and child stunting and underweight. The analyses reveal that childbirth spacing between 24 to 35 months (OR = 0.6, 95% CI [0.4, 1.0]; p < .1), 36 to 47 months (OR = 0.4, 95% CI [0.3, 0.7]; p < .01), and beyond 47 months (OR = 0.5, 95% CI [0.3, 0.9]; p < .05) have lower odds of child stunting than children with birth spacing less than 24 months. Children with birth spacing between 24 to 35 months (OR = 0.5, 95% CI [0.3, 1.0]; p < .05), 36 to 47 months (OR = 0.4, 95% CI [0.2, 0.9]; p < .05) and beyond 47 months (OR =0.5, 95% CI [0.3, 0.9]; p < .05) have lower odds of being underweight than those with birth spacing less than 24 months. The findings reveal a negative association between shorter birth spacing and child stunting and underweight, which suggests that shorter birth spacing is associated with higher odds of child malnutrition. The study recommends that Ghana Health Service and other healthcare providers should educate mothers on the gains of birth spacing of at least 2 years for their children.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This study was conducted with support from the United States Agency for International Development (USAID) through The DHS Program (#720-OAA-18C-00083). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government.